The Effect Of Green Accounting, Corporate Social Responsibility, Profitability And Investment Decisions On Firm Value - Siska Alawiyah (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtion emprical evidence on the Effect of Green Accounting, Corporate Social Responsibility, Profitability, and Invesment Decisions on Firm Value. Design/methodology/approach – This study uses a type of quantitative research, the sample in this study is a raw materials sector company listed on the Indonesia Stock Exchange in 2021-2024 as many as 20 companies. The analytical technique used to test the lupotests is multiple regression analysis using e-views 9 software. Findings – The results of this study found that green accounting has a negative and statistically insignificant effect on firm value, as well as corporate social responsibility has a negative and statistically significant effect on firm value. while profitability has a positive and statistically significant effect on firm value. then investment decisions have a positive and statistically significant effect on firm value. Originality/value: This study discusses Firm Value and other factors such as Green Accounting. Corporate Social Responsibility, Profitability, and Investment Decisions that focus on raw materials sector companies.